Challenges for Modern Monetary Policy - Nikola Fabris (Journal of Central Banking Theory and Practice, 2018)
The first central banks were founded in the XVII century and monetary policy has been evolving ever since. Knowledge on monetary economy has improved significantly over the last couple of decades and a consensus has been reached in a number of areas. As a result, hyperinflations have been extremely rare over the past decades. The global financial crisis challenged traditional monetary policy that was based on the approach involving one instrument (reference interest rate) and one goal (price stability). It is obvious that we need a new approach to monetary policy and I believe that changes will happen gradually in the future. This paper consists of two parts. The first part covers the traditional monetary policy and deals with issues where consensus has been reached, as well as with issues on monetary policy objectives, transparency, and macroprudential policy. The second part addresses the issues that pose a challenge for monetary policy and for which there is no complete consensus. This part elaborates on the dilemma involving rules versus discretions, a new approach to banking supervision, monetary policy during a crisis, the role of econometric models, and the need for international coordination of monetary policy.
Keywords: E50; E52; E58; 330; Monetary Policy; Challenges; Financial Stability; Unconventional Monetary Policy Instruments.